Description of Symptoms Caused by the Infection of the Sars-Cov-2 B.1.621 (Mu) Variant in Patients with Complete Coronavac Vaccination Scheme: First Case Report from Santiago of Chile - Sandino-Garcia, A; Imarai-Bahamonde, C; Acuna-Castillo, C; Valdes-Henriquez, D; Milla-Brito, L; Luraschi-Vargas, R; Barrera-Ávalos, C; Reyes-Lopez, F; Vallejos-Vidal, E; Inostroza-Molina, A (Frontiers Media S.A., 2022)
Vaccine administration is one of the most efficient ways to control the current coronavirus disease 2019 (COVID-19) pandemic. However, the appearance of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants can avoid the immunity generated by vaccines. Thus, in patients with a complete vaccine schedule, the infection by SARS-CoV-2 may cause severe, mild, and asymptomatic manifestations of the disease. In this case report, we describe for the first time the clinical symptoms of four patients (three symptomatic; one asymptomatic) from Santiago of Chile, with a complete vaccination schedule with two doses of CoronaVac (Sinovac Life Science) infected with the variant of interest (VOI) B.1.621 (Mu). They were compared with four unvaccinated patients, who had a higher prevalence of symptoms after infection compared to vaccinated patients. In the CoronaVac-vaccinated group, an 80-year-old patient who registered various comorbidities required Invasive mechanical ventilation for 28 days with current home medical recovery discharge. By contrast, in the unvaccinated group, a 71-year-old presented more symptoms with more than 45 days of Invasive mechanical ventilation, which continues to date, presenting greater lung damage than the vaccinated hospitalized patient. This first report evidence differences in the clinical symptomatology of patients vaccinated and non-vaccinated infected with the VOI B.1.621 (Mu) and suggest the protective effects of CoronaVac against this variant. Copyright © 2022 Barrera-Avalos, Luraschi, Acuña-Castillo, Vidal, Mella-Torres, Inostroza-Molina, Vera, Vargas, Hernández, Perez, Vallejos-Vidal, Valdés, Imarai, Reyes-López and Sandino.